Pilot study: Burnout among pharmaceutical sector’s employees in Serbia and The Republic of Srpska - Janjić, Želimir; Zdjelar, Branislava; Gaković Ranisavljević, Estela; Novaković, Radojka; Arsić, Tanja (Archives of Pharmacy, 2022)
Burnout syndrome is defined as the result of chronic stress in the workplace that has not been successfully resolved. The aim of this research is to examine attitudes of employees in the pharmaceutical sector towards burnout and to examine factors leading to burnout in specific population groups (both pharmacists and technicians) in Serbia and the Republic of Srpska, BiH. Anonymous web-based survey was conducted in May and June 2022 via social networks. Socio-demographic parameters were followed and Maslach burnout inventory with 22 questions (translated into Serbian) was used to assess burnout among employees. Microsoft Excell was used for statistical analysis. There were 184 respondents. Over 92% (170) of which were female, and 66,3% were in the middle-aged group (between 31 and 50 years old). 17.4% (32) were technicians and the rest had master’s degree or above in pharmacy. 156 of 184 (85%) worked in a public pharmacy. The majority of respondents works in Serbia (52.2%). 162 out of 184 respondents consider themselves to have had burnout during the last year, and about 40% very frequently consider job change. Respondents felt frequent emotional exhaustion from working with patients (53% several times a week or more). However, majority (65%) felt they have a positive impact on others through their work almost every day. This pilot research concluded there is a great chance of pharmacy employees having burnout; both in Serbia and Republic of Srpska. Further studies with bigger and more homogenous samples are needed to estimate levels of burnout in different subgroups.